Interdisciplinary Approaches to Business Education: Bridging Theory and Practice - Paul (Sr.), Stanley A. V.; Paul (Jr.), Stanley A. V. (Integrated Journal for Research in Arts and Humanities, 2024)
Business education is at a critical juncture where the integration of interdisciplinary approaches is essential to bridge the gap between theoretical knowledge and practical application. This article explores the necessity and benefits of incorporating interdisciplinary methods into business education. It examines current practices, proposes strategic frameworks for implementation, and discusses the implications for both educators and students. By leveraging insights from various disciplines, business education can be transformed to produce well-rounded graduates equipped with the skills needed to navigate the complexities of the modern business environment.